The small finds and vessel glass from Insula VI.1 Pompeii : excavations 1995-2006 - Cool, H. E. M., (Archaeopress Roman archaeology ;, 2016)
This report presents the vessel glass and small finds found during the excavations between 1995 and 2006 that took place in Insula VI.1, Pompeii (henceforth VI.1). More than 5,000 items are discussed, and the size of the assemblage has meant that the publication is in two parts.